Analyzing Ferroresonance Phenomena in Power Transformers Including Zinc Oxide Arrester and Neutral Resistance Effect. (30th July 2012) - Radmanesh, Hamid; Seyed Hamid, Fathi
Abstract : This paper studies the effect of zinc oxide arrester (ZnO) and neutral earth resistance on controlling nonconventional oscillations of the unloaded power transformer. At first, ferroresonance overvoltage in the power system including ZnO is investigated. It is shown this nonlinear resistance can limit the ferroresonance oscillations but it cannot successfully control these phenomena. Because of the temperature dissipation of ZnO, it can withstand against overvoltage in a short period and after that ferroresonance causes ZnO failure. By applying neutral earth resistance to the system configuration, mitigating ferroresonance has been increased and chaotic overvoltage has been changed to the smoother behavior such as fundamental resonance and periodic oscillation. The simulation results show that connecting the neutral resistance exhibits a great mitigating effect on nonlinear overvoltage.